Seismic Risk Assessment of Urban and Rural Settlements around Lake Malawi - Goda, Katsuichiro; Gibson, Emily Daisy; Smith, Holly R.; Biggs, Juliet; Hodge, Michael (Frontiers in Built Environment, 2016)
The seismic risk potential for Malawi is high because traditional adobe and earthen structures are seismically vulnerable and large earthquakes of Mw7.0 or greater can be originated from the Malawi Rift. To assess seismic risk of the Malawian communities quantitatively, data and models for exposure, hazard, and vulnerability modules that are suitable for Malawi are integrated. The developed risk model is applied to a retrospective appraisal of the past damaging 2009 Karonga earthquake sequence and to the future earthquake scenarios for long-term risk management purposes. The earthquake impact assessment results highlight that the collapse risk predictions of the Malawian settlements are particularly dependent on the inclusion of large-magnitude earthquakes from the active faults around Lake Malawi and the selection and combination of seismic vulnerability models.